Single-cell sequencing of the substantia nigra reveals microglial activation in a model of MPTP - Liu, Qing; Liu, Ziyu; Xie, Wenmeng; Li, Yibo; Wang, Hongfang; Zhang, Sanbing; Wang, Wenyu; Hao, Jiaxin; Geng, Dandan; Yang, Jing; Wang, Lei (Frontiers in Aging Neuroscience, 2024)
Parkinson's Disease (PD) is a neurodegenerative disease, but the exact disease etiology remains largely unknown. N-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) is a neurotoxin widely used to induce PD models, but the effect of MPTP on the cells and genes of PD has not been fully elucidated. Therefore, single-nucleus RNA sequencing was performed in the Substantia Nigra (SN) of MPTP mice. Initially, we observed specific Differentially Expressed Genes (DEGs) and PD risk genes enrichment in microglia and obtained the functional phenotype changes in microglia. Next, we found that inter-cellular crosstalk was important in regulating the functional phenotype changes of microglia. Finally, subpopulation reconstruction and pseudotime analysis revealed the activation state of microglia and revealed a pro-inflammatory trajectory characterized by transcription factors Nfe2l2 and Runx1. Our work summarized the state changes of SN microglia in MPTP mice and provided a new opportunity for the study of the pathogenesis of PD.